Diagnostic tools for rapid eye movement sleep behaviour disorder - Cooray, N (2020)
There is clear evidence to support Rapid-Eye-Movement (REM) sleep behaviour disorder (RBD) as an early predictor of Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy. Those diagnosed with RBD enact their dreams and therefore present an abnormal characteristic of movement during REM sleep. This unusual sleep disorder presents an opportunity to better understand neurological degeneration and in-turn develop preventative medicine. However, manual polysomnograph (PSG) analysis is mandatory when diagnosing RBD, which demands complex monitoring equipment, specially trained staff, bed availability, and clinicians to interpret abundant amounts of data. Inevitably this process is time consuming and expensive, creating a demand for automated diagnostic support tools to better utilise the time of clinicians.